Bioinspired phase-separated disordered nanostructures for thin photovoltaic absorbers - Siddique, Radwanul H. (Sci Adv, 2017)
The wings of the black butterfly, Pachliopta aristolochiae, are covered by micro- and nanostructured scales that harvest sunlight over a wide spectral and angular range. Considering that these properties are particularly attractive for photovoltaic applications, we analyze the contribution of these micro- and nanostructures, focusing on the structural disorder observed in the wing scales. In addition to microspectroscopy experiments, we conduct three-dimensional optical simulations of the exact scale structure. On the basis of these results, we design nanostructured thin photovoltaic absorbers of disordered nanoholes, which combine efficient light in-coupling and light-trapping properties together with a high angular robustness. Finally, inspired by the phase separation mechanism of self-assembled biophotonic nanostructures, we fabricate these bioinspired absorbers using a scalable, self-assembly patterning technique based on the phase separation of binary polymer mixture. The nanopatterned absorbers achieve a relative integrated absorption increase of 90% at a normal incident angle of light to as high as 200% at large incident angles, demonstrating the potential of black butterfly structures for light-harvesting purposes in thin-film solar cells.